(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2024)
Malaysia has ratified the 1982 United Nation Convention Law of the Sea (UNCLOS) 1982 and uses this convention as a guide to govern the country’s territorial sea. In 2012, the Territorial Sea Act was issued by the government as an initiative to implement UNCLOS 1982 domestically. However, Territorial Sea Act 2012 does not properly govern innocent passage in territorial waters. This Act is not sufficient to ensure that the governance of Malaysian innocent passage can be implemented domestically. The objective of this study is to observe the history and development of the concept of innocent passage in the territorial sea, to identify the provisions of the right of innocent passage in the territorial sea under the UNCLOS 1982 and to study the implementation of the innocent passage in the domestic laws of Malaysia and Australia and to suggest improvements that can be executed by Malaysia in strengthening domestic laws regarding innocent passage. The research methodology used in this study is qualitative through armchair method, comparative method and critical analysis method. The findings of this study is that Malaysia does not have a comprehensive domestic law for innocent passage while Australia has directly adapted the provision of UNCLOS 1982 related to innocent passage in the territorial sea into its domestic law. Suggested improvements that can be made is that Malaysia emulates Australia to adapt the provisions of UNCLOS 1982 directly into the Territorial Sea Act 2012, the drafting of a new act specifically for innocent passage, and reorganization of the set of domestic laws of the sea. Keywords: Maritime, law of the sea, territorial sea, UNCLOS 1982, innocent passage, international law Full text: PDF